Postmortem Dissections of Common Targets for Lesion and Deep Brain Stimulation Surgeries. Issue 6 (26th August 2019) - Holanda, Vanessa M; Okun, Michael S; Middlebrooks, Erik H; Gungor, Abuzer; Barry, Margaret E; Forder, John; Foote, Kelly D
Abstract: BACKGROUND: The subthalamic nucleus (STN), globus pallidus internus (GPi), and pedunculopontine nucleus (PPN) are effective targets for deep brain stimulation (DBS) in many pathological conditions. Previous literature has focused on appropriate stimulation targets and their relationships with functional neuroanatomic pathways; however, comprehensive anatomic dissections illustrating these nuclei and their connections are lacking. This information will provide insight into the anatomic basis of stimulation-induced DBS benefits and side effects. OBJECTIVE: To combine advanced cadaveric dissection techniques and ultrahigh field magnetic resonance imaging (MRI) to explore the anatomy of the STN, GPi, and PPN with their associated fiber pathways. METHODS: A total of 10 cadaveric human brains and 2 hemispheres of a cadaveric head were examined using fiber dissection techniques. The anatomic dissections were compared with 11.1 Tesla (T) structural MRI and 4.7 T MRI fiber tractography. RESULTS: The extensive connections of the STN (caudate nucleus, putamen, medial frontal cortex, substantia innominata, substantia nigra, PPN, globus pallidus externus (GPe), GPi, olfactory tubercle, hypothalamus, and mammillary body) were demonstrated. The connections of GPi to the thalamus, substantia nigra, STN, amygdala, putamen, PPN, and GPe were also illustrated. The PPN was shown to connect to the STN and GPi anteriorly, to the cerebellum inferiorly, and to the substantia nigra anteriorly and superiorly. CONCLUSION: This study demonstrates connections using combined anatomic microdissections, ultrahigh field MRI, and MRI tractography. The anatomic findings are analyzed in relation to various stimulation-induced clinical effects. Precise knowledge of neuroanatomy, anatomic relationships, and fiber connections of the STN, GPi, PPN will likely enable more effective targeting and improved DBS outcomes.